Schinus terebinthifolius Raddi (Aroeira) leaves oil attenuates inflammatory responses in cutaneous wound healing in mice - Moura Estevao, Ligia Reis (2017)
Purpose: To investigated the inflammatory, angiogenic and fibrogenic activities of the Schinus terebinthifolius Raddi leaves oil (STRO) on wound healing. Methods: The excisional wound healing model was used to evaluate the effects of STRO. The mice were divided into two groups: Control, subjected to vehicle solution (ointment lanolin/vaseline base), or STRO-treated group, administered topically once a day for 3, 7 and 14 days post-excision. We evaluated the macroscopic wound closure rate